Tales of horror - Poe, Edgar Allan (London: Alma Classics, 2017)
A collection of the best works by master of the detective, horror, and science fiction genres, Edgar Allen Poe
Includes notes
Keywords: Horror fiction; Horror tales, American; Short stories